A wide dynamic range CMOS image sensor with the optimum photoresponse per pixel - Das, D; Mills, H; Collins, S; IEEE (2011)
A 100x100 CMOS image sensor (CIS) occupying an area of 2.25 mm2 fabricated in a standard 0.35-m CMOS technology is described. A back to back pixel layout with pixel dimension of 10m10m and a fill factor of 41% is achieved. The pixels in the CIS integrate the photocurrent for time that depends upon the photocurrent to map wide dynamic range (WDR) real world scenes to low DR display medium. Nonlinear functions or tone mapping operators such as the logarithmic function based on the luminance and other pixel parameters is implemented by the CIS. Two methods to optimize the logarithmic tone mapping operator for improved low light performance are proposed and results of their implementation in hardware presented. © 2011 IEEE.